Turgut Cansever’s Beyazit Square in the Light of His Theoretical Constructions - Civelek, Yusuf; Düzenli, Halil Ibrahim (Journal of Islamic Architecture, 2025)
This paper addresses the historical significance of Turgut Cansever’s project for the redesign of the Beyazıt Square in Istanbul owing to its effort to recreate the particularity of a place through the articulation of motion, orientation, and ornamentation. The paper argues that the Beyazıt Square project is crucial for Cansever’s construction of an aesthetic based on the Islamic ‘world-conception’ through the interpretation of texts, as well as historic and modern places and buildings. Therefore, this study aims to demonstrate that Cansever’s Beyazıt Square project, initiated in 1960, is one of the earliest and most notable manifestations of his theoretical concepts. The methodology of the study relies on investigating the correlation between the partially applied project and the architect’s theoretical ideas, which he developed through intertextual readings on architecture, philosophy, and religion, with a particular focus on Sufism. This concept has evolved. The sources of the investigation include texts written by the architect or others on his work since 1949, the original drawings of the project, and the physical changes that the square underwent between 1505 and the present day. Personal communications with the daughter and son-in-law of Cansever, who are also architects and have collaborated with him for a long time, are valuable sources for this investigation. This study demonstrates that the fundamentals of Cansever’s theoretical ideas predate 1960, with the majority emerging in a more articulate form through his writings, interviews, and speeches after 1980. It shows that Cansever made connections between the main precepts of Modernism and his interpretation of the Islamic principles of art and architecture around 1960. It also makes clear that the recent adaptation of the unfinished project in 2023 is due to the relevance of these theoretical ideas for the popular but relatively weak pursuits of discovering and reconnecting with the principles and values of the Islamic built environment. Perhaps the most important benefit of this text lies in its presentation of the application of spatial and phenomenological concepts by a non-Western, Muslim architect in a public space.